Pleurotus eryngii Genomes Reveal Evolution and Adaptation to the Gobi Desert Environment - Dai, Yueting; Sun, Lei; Yin, Xiaolei; Gao, Meng; Zhao, Yitong; Jia, Peisong; Yuan, Xiaohui; Fu, Yongping; Li, Yu (Frontiers in Microbiology, 2019)
Pleurotus eryngii (King Oyster) is one of most highly prized edible mushrooms. Within this species, P. eryngii var. eryngii distributed worldwide, while P. eryngii var. ferulae only distributed in Europe and China, especially adapted to the Gobi Desert in Xinjiang Autonomous Region of China. However, little is known about its genome-wide pattern of evolution and adaptation to divergent environments. Here, we present the high-quality genome sequences of P. eryngii var. eryngii strain PEE81 originating from Europe and P. eryngii var. ferulae strain PEF12 originating from the Gobi Desert of China. The assembly genome size of PEE81 and PEF12 was 53.6 Mb and 48.0 Mb respectively, which are larger than other reported genomes in the genus Pleurotus. We suggest that the selective amplification of long terminal repeat (LTR) retrotransposon increase the genome size of the genus Pleurotus and may play a key role in driving their rapid species diversification. Molecular clock analyses of five Pleurotus species including PEE81, PEF12, P. tuolensis, P. ostreatus and P. cf. florida suggest the molecular evolution of the genus Pleurotus over time scales ranging from ~4 to ~38 million years ago (Mya), and PEE81 and PEF12 diverged ~13 Mya. We then performed the genome resequencing of 33 geographically diverse strains of P. eryngii var. eryngii and var. ferulae and investigated genome variation among and within these two populations. Further comparing analyses of these two populations detected several candidate genes related to stress responses and DNA repair that are putatively involved in adaptation to the Gobi Desert environment. These findings offer insights into genome evolution of the genus Pleurotus and provide valuable genomic resources for King Oyster breeding.